(untitled) (Journal of Comparative & International Higher Education, 2024)
The war in Ukraine has opened a Pandora’s Box of internationalization concerns that, heretofore, took a backseat to concerns with the effectiveness and sustainability of the field. In analyzing the impact of the war on international higher education, scholars offered various assessments of the conflict’s effects, especially in the combatant countries and post-Soviet Eurasia: e.g., the disruption of organizational forms and methods of internationalization in Ukraine, the forced relocation of international students and faculty, and the creation of special programs to accommodate transferring international students from Russian and Ukrainian universities. Each of these assessments catches aspects of the emerging reality. Yet, they miss a crucial change that the war has triggered: ideational change regarding the rationales, norms, and values that underpin internationalization and shape the behavior of states and other related actors. Through this work, I advance this line of inquiry and examine its problematic implications for policy and practice.